Creation of an Experimental Series of Vaccine Against Infectious Necrotic Hepatitis of Sheep and Determination of its Sterility and Injury - Shorasul, Hakimov; Khaitovich, Salimov Ilkhom (American Journal of Biology and Natural Sciences, 2026)
This article presents the technology for producing a vaccine against infectious necrotic hepatitis in sheep and the results of scientific research on the development of a pilot series from the local epizootic strain J-22 isolated in 2022. It also presents the results of studies conducted to determine the sterility and safety of the prepared vaccine series.